Modernising Lenin's Russia : Economic Reconstruction, Foreign Trade and the Railways. - Heywood, Anthony (Cambridge Russian, Soviet and post-Soviet studies ;, 1999)
This book reassesses Bolshevik attitudes towards economic modernisation and foreign economic relations under Lenin. It examines the decision to import vast quantities of railway equipment in order to achieve rapid economic modernisation, and reveals the scale of Bolshevik business dealings with the capitalist West immediately after the Revolution.